Metal-free branched alkyl tetrathienoacene (TTAR)-based sensitizers for high-performance dye-sensitized solar cells. Issue 24 (30th May 2017) - Ezhumalai, Yamuna; Lee, Byunghong; Fan, Miao-Syuan; Harutyunyan, Boris; Prabakaran, Kumaresan; Lee, Chuan-Pei; Chang, Sheng Hsiung; Ni, Jen-Shyang; Vegiraju, Sureshraju; Priyanka, Pragya; Wu, Ya-Wen; Liu, Chia-Wei; et al.
Abstract : New branched alkyl tetrathienothiophene (TTAR)-based organic sensitizers with power conversion efficiency up to 11%. Abstract : A new series of metal-free alkylated tetrathienoacene (TTAR)-based organic chromophores, TPA–TTAR–TA (R = branched-C8 H17, 1, TTAR-b8 ; R = C15 H31, 2, TTAR-15 ; R = C9 H19, 3, TTAR-9 ), are synthesized for application in dye-sensitized solar cells (DSSCs). Due to the extensively conjugated TTAR π-bridge, all three dyes exhibit high extinction coefficients (1 × 10 5 M −1 cm −1 ). By systematically exploring the effects of the TTAR alkyl chain substituents, a significant influence of the dye coverage (orientation) on the TiO2 surfaces is observed. The branched-alkylTTAR-b8 (1 ) promotes significant tilting and packing distortion on TiO2 in comparison to more ordered monolayers of linear long alkylsTTAR-15 (2 ) andTTAR-9 (3 ). Photophysical measurements on the dye-grafted TiO2 films reveal that the branched-alkylatedTTA unit in1 enhances the electron injection efficiency, in agreement with the high quantum efficiency. Notably, by utilizing a three-dimensional (3D) photonic crystal (PhC) layer to enhance the coherent scattering an increase the light absorption, TTAR-b8 exhibits higher short-circuit current densities and achieved a high PCE of 11.18%.TTAR-b8 is thus the best performing fused-thiophene-based organic DSSC dye reported to date.